Orang Laut, Bajak Laut, dan Raja Laut: Dinamika Kehidupan dan Kekuasaan dalam Naskah Kontrak Sultan-sultan Palembang Abad 18-19 - Endang Rochmiatun (Masyarakat Pernaskahan Nusantara, 2016)
Sriwijaya Kingdom and Palembang Sultanate were the maritime empires that could not be separated from an understanding of the sea. The role of sea as a liaison with other regions also made their knowledges opened, because any information and knowledge from the outside world or otherwise entered through the sea. The Manuscript Kontrak Sultan-Sultan Palembang of 18-19 centuries reveal the dynamics of the life and power of the sea.